(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
In this article, parents in a place called family the influence of a person’s position in the family and their fairness in the distribution of roles on the development of children, and that the environment created by the family is one of the psychological factors that serve to ensure the influence of young people on the formation of their perceptions of the family.